2018
DOI: 10.2106/jbjs.oa.17.00056
|View full text |Cite
|
Sign up to set email alerts
|

Subscapularis Repair Is Unnecessary After Lateralized Reverse Shoulder Arthroplasty

Abstract: Background:Controversy exists as to whether the subscapularis should be repaired after reverse shoulder arthroplasty. The purpose of the present study was to evaluate the utility of repairing the subscapularis after reverse shoulder arthroplasty with regard to complications, objective findings, and patient-reported outcome measures.Methods:We retrospectively reviewed the records for 99 patients who had undergone a lateralized reverse shoulder arthroplasty with (n = 58) or without (n = 41) subscapularis repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“… 38 Additionally although some reports have found absence of subscapularis repair being significantly associated with prosthetic instability, 40 others found no difference between repair vs. no repair, 261 and using a lateralized RSA subscapularis repair may not be necessary. 207 …”
Section: Discussionmentioning
confidence: 99%
“… 38 Additionally although some reports have found absence of subscapularis repair being significantly associated with prosthetic instability, 40 others found no difference between repair vs. no repair, 261 and using a lateralized RSA subscapularis repair may not be necessary. 207 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Roberson et al 20 found no functional outcome, range of motion, or complication differences in 99 patients with and without subscapularis repair using lateralized glenoid prostheses. However, in the subscapularis repair subset, patients who underwent a subscapularis peel and repair had better change in forward elevation (26° more) compared with the tenotomy and repair group, but had similar American Shoulder and Elbow Surgeons and Penn Shoulder scores 20 . Friedman et al 7 reported on 591 primary RSA patients comparing functional outcomes with and without subscapularis repair using a lateralized humeral implant showing no difference in range of motion or outcomes scores between the groups.…”
Section: Discussionmentioning
confidence: 92%
“…One study found that RSA with glenosphere lateralization (+3 or +6 mm) had worse improvements in American Shoulder and Elbow Surgeons scores if the subscapularis tendon was repaired 25 . In contrast, Roberson et al 20 found no functional outcome, range of motion, or complication differences in 99 patients with and without subscapularis repair using lateralized glenoid prostheses. However, in the subscapularis repair subset, patients who underwent a subscapularis peel and repair had better change in forward elevation (26° more) compared with the tenotomy and repair group, but had similar American Shoulder and Elbow Surgeons and Penn Shoulder scores 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical studies have evaluated COR, humeral neck-shaft angle, humeral offset, humeral version, glenosphere diameter, superior-inferior glenosphere positioning, implant tilt, as well as soft tissue repair of the rotator cuff. 1 , 8 , 16 , 18 , 19 , 20 , 21 , 30 , 34 , 35 All these factors must be considered when evaluating implant design and implantation techniques.…”
Section: Discussionmentioning
confidence: 99%